(untitled) (Szociológiai Szemle, 2024)
In March 1995 we conducted a survey on strength and tenacity of antisemitic prejudicies in Hungary. 1500 personal interviews were carried out on the basis of a standardized questionnaire. The group surveyed was representative of the total adult Hungarian population (over 18 years of age) in terms of gender, age, place of residence, and educational qualification. The results indicate that one-quarter of the present adult Hungarian population my be classed as antisemitic. However, one of the greatest problems of empirical research on prejudice is that we must draw conclusion about the prejudice of members of the surveyed groups on the basis of opinions that prejudiced people in particular may be reluctant to express openly under certain social conditions. Research on antisemitism has revealed an especially strong latency pressure among respondents. Therefore, the question in whether it is necessary to adjust results obtained on the basis of opinions openly expressed in the course of the interviews. For our examination of latent antisemitism, we used a group of questions that had already been used in three other surveys. The first group of questions measure the extent to which latency pressure is felt, and allow us to examine where individuals inclining to latency are placed on the antisemitism scale: The second group of questions indicate how strong the various respondents consider antisemitism to be in society, and-on the basis of their position on the antisemitism scale-whether they see themselves belonging to what they consider to be the majority or the minority. This analysis is important if we wish to estimate latency, because previous research has shown that certain groups react to the latency pressure by projecting their real opinions on to other people, in particular on to ’the majority of society’. Finally, we assessed whether individual respondents consider a series of statements expressing to a greater or lesser extent antisemitic views to be antisemitic or not. We may consider the negative responses to indicate latency, because respondents may be able to dissolve the cognitive dissonance stemming from the illegitimate nature of their suppressed antisemitic views, by declaring these views to be nonantisemitic (i.e. legitimate). On the basis of the responses to the three groups of questions indices were prepared which were then used as indicators of latency. Based on the results of the measurement of latency, we found that we should adjust our estimate of the size of the antisemitic groups by a minimum of 2% and a maximum of 10%.